Aggregator: a machine learning approach to identifying MEDLINE articles that derive from the same underlying clinical trial - Shao, Weixiang; Adams, Clive E.; Cohen, Aaron M.; Davis, John M.; McDonagh, Marian S.; Thakurta, Sujata; Yu, Philip S.; Smalheiser, Neil R. (Elsevier, 2015)
Objective